2020
DOI: 10.2139/ssrn.3562570
|View full text |Cite
|
Sign up to set email alerts
|

Spillover of COVID-19: Impact on the Global Economy

Abstract: How did a health crisis translate to an economic crisis? Why did the spread of the coronavirus bring the global economy to its knees? The answer lies in two methods by which coronavirus stifled economic activities. First, the spread of the virus encouraged social distancing which led to the shutdown of financial markets, corporate offices, businesses and events. Second, the exponential rate at which the virus was spreading, and the heightened uncertainty about how bad the situation could get, led to flight to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
900
1
67

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 1,055 publications
(985 citation statements)
references
References 10 publications
17
900
1
67
Order By: Relevance
“…Several markets reacted to the pandemic and a number of industries were affected from the COVID-19 shock (Ozili and Arun, 2020). The global demand for air travel, including travel in and out of Africa, dropped significantly and the resulting loss of revenue was estimated at US$113bn according to the International Air Transport Association (IATA) estimates.…”
Section: Socioeconomic Impact: Understanding Market Reactions In Africamentioning
confidence: 99%
“…Several markets reacted to the pandemic and a number of industries were affected from the COVID-19 shock (Ozili and Arun, 2020). The global demand for air travel, including travel in and out of Africa, dropped significantly and the resulting loss of revenue was estimated at US$113bn according to the International Air Transport Association (IATA) estimates.…”
Section: Socioeconomic Impact: Understanding Market Reactions In Africamentioning
confidence: 99%
“…9. Business continuity and workplace public health measures: Business continuity is an important domain in the societal response for COVID-19, as public health measures have negative spill over effects on the economy [33] . MOH as the grassroots health manager had to take the leadership role according to the government circulars and guidelines to restore the economy.…”
Section: Resultsmentioning
confidence: 99%
“…Existing literature found diverse results in these regards. Ozili and Arun (2020) have conducted an empirical study on the effect of social distancing policy that was adopted to prevent the spread of the Corona Virus, based on four continents: North America, Africa, Asia, and Europe. The study found that 30 days of social distancing policy or lockdown hurts the economy through its negative impact on stock prices.…”
Section: Literature Reviewmentioning
confidence: 99%
“…week from 24 th to 28 th February (Ozili and Arun, 2020). The market value of Standard & Poor (S&P) 500 indexes declined to 30% since the Covid-19 outbreak.…”
mentioning
confidence: 99%